Effect of Sulphur Content on Crystallization Characteristics and Mechanical Properties of trans-Polyisoprene - Fu, Wen; Liu, Anhua; Li, Jianxiong; Wang, Li (Asian Journal of Chemistry, 2014)
The effect of sulphur content on crystallization behavior of vulcanized trans-1,4-polyisoprene (TPI) was examined with optic microscope and differential scanning calorimetry. The dynamic mechanical properties were investigated with dynamic mechanical analyzer and the mechanical properties and shape memory performance were also determined. The results showed that crystallinity and spherulite size decreased with the increase of sulphur content. The crystals disappeared completely at sulphur content of 4 phr. The fusion heat and melting temperature of trans-1,4-polyisoprene crystals decreased with the increase of sulphur content. Dynamic mechanical analyzer revealed a striking change in the loss tangential as the sulphur content changed from 3-4 phr. When the sulphur content increased, the tensile strength, the modulus, the drum abrasion resistance and the shore A hardness of trans-1,4-polyisoprene decreased, while the resiliency increased. trans-1,4-Polyisoprene could maintain the performance of shape memory as the sulphur content was below 3 phr but the shape memory feature disappeared as the sulphur content was over 4 phr.